The Effect of Different Periodization and Modes of Concurrent Strength and Endurance Training on Double Poling Performance and Body Composition in Adolescent Cross-Country Skiers - Eno Vahtra; Rasmus Pind; Evelin Mäestu; Priit Purge; Priit Kaasik; Jarek Mäestu (MDPI AG, 2022)
The aim of the study was to compare the effects of different types and periodization of strength training on body composition and maximal aerobic performance in 10-week training period in adolescent XC skiers. Twenty-eight adolescent competitive cross-country skiers, including 10 females (age 17.9 ± 1.8 years; body mass 69.6 ± 9.7 kg; height 1.77 ± 0.1 m; training experience 8.6 ± 3.2 years) took part in this study. Pre-and post-intervention performance was measured with the incremental exercise test (Pmax) on a double poling ski ergometer. Changes in body composition were measured with DXA. In addition to regular endurance training, experimental group one (EXP1) performed maximal and explosive strength training two times per week, experimental group two (EXP2) performed maximal and explosive strength training 1-3 times per week, and the traditional (TRAD) group performed low intensity-high volume strength training 2 times per week. Increases in arm, trunk, and overall lean mass were found in TRAD (p < 0.05). Increases in arm lean-mass was found in EXP1 (p < 0.05), while no changes in body composition occurred in EXP2 (p ≥ 0.05). Pmax improved significantly in all groups (p < 0.05). Changes in body mass, overall and arm lean mass was related to changes in absolute performance (W; p < 0.05), while no relationships were found between changes in body composition parameters and relative performance (W/kg; p ≥ 0.05). In conclusion, different periodization of strength training led to similar improvements in double poling ergometer performance, but resulted in different changes in body composition (lean mass) in adolescent cross-country skiers.